PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN DI BEI - Jannah, Umi Aniswatur Roudtul; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to examine the influence of financial performances to the disclosure of sustainability report (SR). The financial performances that have been employed in this research are profitability, liquidity, leverage, and activity. The population is all companies which are listed in Indonesia Stock Exchange in 2010-2014 periods. The selection of research samples has been carried out by using purposive sampling method. Based on the purposive sampling method, it has been found that the numbers of the companies which have published their sustainability report are 11 companies. The analysis methods that have been implemented in this research are multiple regressions analyses, classic assumption test, model feasibility test, determination coefficient test and hypothesis test which have carried out by using SPSS 20 version. The result of the research shows that profitability variable and liquidity has positive influence to the disclosure of sustainability report. Meanwhile, the leverage variable and activity does not have any significant influence to the disclosure of sustainability report. The result of the test in the research proves that 25% of the dependent variable can be explained by the independent variables and the remaining by 75% is influenced by other variables beyond the independent variables.Keywords: Sustainability Report, Financial Performance, Multiple Regressions Analysis